Digital Transformation: Towards a model for competency-based governance of digital transformation for boards of directors in South Africa - Siwahla-Madiba, Nandipha, Daphne; Costa, King (My University, 2022)
The requirement for directors of boards to attain competencies in relation to governance of digital transformation is evidently increasing at global level. South Africa, as a player within the global economic landscape, cannot afford to have directors who do not understand the requisite competencies required for governance of digital transformation. Whereas many organisations and boards have implemented new corporate governance codes, principles, and standards, as well as new company legislation, frameworks or models on governance of digital transformation are not yet integrated into functional board activities. This study was hinged upon an interpretivist epistemology, with a case study design used as a strategy for inquiry. Using purposive sampling approach, a total of seven participants were interviewed using a semi-structured interview guide. Ethical considerations were followed in terms of the institutional requirements and participants were requested to sign consent forms for participating in this study. Implications of participations were clearly articulated to participants and their right to discontinue participation at any time was proffered. In this study, their participation is referred to as “Participant” followed by a number, which does not reflect the order of their participation, but to provide anonymity. Data was analysed through a thematic approach, using the COSTA QDA technique on webQDA software. The study findings culminated in three main themes as follows: • There is no standard definition of competence-based models for governance of digital transformation • Governance of digital transformation is perceived as governance of information technology (IT) • There is a need for digital transformation competence at board level Discussion of the meanings attached to these themes resulted in a development of a model entitled MADIBA Model, which is an acronym for six constructs that could be used to guide establishment of a competency model for governance of digital transformation by directors of different boards. Study limitations were mainly due to the fact that only a subjective approach to the inquiry was followed, justified by the fact that the researcher sought to explore in-depth views and perspectives of boards of directors in relation to governance of digital transformation competency model. The study further recommended that there could be another study focusing on pragmatic approaches or even positivistic perspectives, to obtain generalised perspectives on the phenomenon.
Keywords: Competency-Based Model; Digitalization; Digital Transformation; Directors of Boards; Governance; Technology